Fate of nitrogen atoms in the photocatalytic degradation of industrial (congo red) and alimentary (amaranth) azo dyes. Evidence for mineralization into gaseous dinitrogen. (2003) - Puzenat, E.; Lachheb, H.; Karkmaz, M.; Houas, A.; Guillard, C.; Herrmann, J. M.
Abstract : The photocatalytic degradation of two azo-dyes–an industrial one (Congo Red (CR)), and an alimentary one (Amaranth (AM))–has been investigated inTiO 2 /UV aqueous suspensions. In addition to a prompt removal of the colors, TiO 2 /UV-based photocatalysis was simultaneously able to fully oxidize the dyes, with a complete mineralization of organic carbon intoCO 2 . In particular, the aromatic rings were submitted to successive attacks by photogeneratedOH ∘ radicals leading to hydroxylated metabolites before the ring opening and the final evolution ofCO 2 induced by repeated subsequent "photo-Kolbe" reactions with carboxylic intermediates. Simultaneously, sulfur heteroatoms were converted into innocuousSO 4 2 − ions. The mineralization of nitrogen was more complex to analyze. Nitrogen atoms in the -3 oxidation state, such as in the amino-groups of CR, initially remained at this reduction degree and producedNH 4 + cations, subsequently and very slowly converted intoNO 3 − anions. For both azo-dyes (CR and AM) degradation, the overall mass balance in nitrogen was always found incomplete. Various experiments performed in pure oxygen in a vacuum-tight cell and then in an air-free photoreactor (but filled with pure oxygen) enabled us to put in evidence the formation ofN 2 . Quantitative measurements clearly indicated that gaseous dinitrogen evolved stoichiometrically corresponded to the mineralization of the central –N=N– azo-group. This constitutes the ideal issue for the elimination of nitrogen-containing pollutants, not only for environmental photocatalysis but also for any other physicochemical method. These results suggest thatTiO 2 /UV photocatalysis may be envisaged as a method for treatment of diluted colored waste waters not only for decolorization but also for total detoxification, in particular in textile industries in semi-arid countries.